Risk factors for accidental dural puncture during epidural anesthesia for laboring women. (1st September 2016) - Michaan, Nadav; Lotan, Michael; Galiner, Masha; Amzalag, Sagi; Many, Ariel
Abstract: Background and objectives : Accidental dural puncture (ADP) during epidural analgesia is a debilitating complication. Symptoms of ADP post-dural puncture headache (PDPH) are headache while rising from supine to upright position, nausea, and neck stiffness. While age, gender and needle characteristics are established risk factors for ADP, little is known about risk factors in laboring women. Methods : All cases of ADP during epidural analgesia treated with blood-patching during a 3-years period were retrospectively reviewed. Each case was matched to two controls according to delivery period. Results : Forty-nine cases of blood patches after ADP out 17 977 epidural anesthesia procedures were identified (0.27%). No differences were found between cases and controls with regards to body mass index, labor stage at time of epidural, length of second stage, location of epidural along the lumbar vertebrae, anesthesiologist's experience or time when epidural was done. In cases of ADP, significantly lower doses of local anesthetics were injected (10.9 versus 13.5 cc, p < 0.001); anesthesiologists reported significantly more trials of epidurals (70 versus 2.8% more than one trial, p < 0.001), more patient movement during the procedure (13 versus 0%, p < 0.001), more intra-procedure suspicion of ADP (69 versus 0%, p < 0.001) and more cases where CSF/blood was drawn with the syringe (57 versus 2.4%, p < 0.001). Conclusion : ADP during labor is a rare but debilitating complication. Risk factors for this iatrogenic complication include patient movement and repeated epidural trials. Intra-procedure identification of ADP is common, allowing early intervention with blood patching where indicated.